Stochastic Four-State Mechanochemical Model of F1-ATPase - 吴魏霞 展永 赵同军 韩英荣 陈娅斐 (Communications in theoretical physics, 2010)
F1-ATPase, a part of ATP synthase, can synthesize and hydrolyze ATP moleculars in which the central γ-subunit rotates inside the α3β3 cylinder. A stochastic four-state mechanochemical coupling model of F1-ATPase is studied with the aid of the master equation. In this model, the ATP hydrolysis and synthesis are dependent on ATP, ADP, and Pi concentrations. The effects of ATP concentration, ADP concentration, and the external torque on the occupation probability of binding-state, the rotation rate and the diffusion coefficient of F1-ATPase are investigated. Moreover, the results from this model are compared with experiments. The mechanochemical mechanism F1-ATPase is qualitatively explained by the model.